Eating patterns of university lecturers: relationship with socioeconomic factors (Research, Society and Development, 2022)
This study aimed to identify the main eating patterns of professors at a University and to associate them with socioeconomic factors. The population consisted of 734 lecturers, with a sample selected that totaled 147 individuals of both sexes, aged 22 to 50 years old. The data collection was conducted through semi-structured interviews and the survey of food consumption made by 24-hour recall. Eating patterns were identified by factor analysis by main components, followed by orthogonal varimax rotation. The adequacy of the data to the factor analysis was confirmed by the Kaiser-Meyer-Olkin coefficient (KMO) and the Barltlet sphericity test to estimate the variables in relation to eating patterns. Three eating patterns were identified: urban, popular and traditional regional. The urban pattern had greater adherence to the occupation time factor and less adherence to the race factor. The popular pattern had a greater association of occupation time and less association with race. The traditional regional pattern shows more evidence of the race factor and less evidence of the marital status factor. The knowledge of the variables associated with the eating patterns of this study can contribute to the planning of the actions of healthy practices in the studied public.